2022
DOI: 10.3389/fmed.2021.835515
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brain-Derived Neurotrophic Factor in Obstructive Sleep Apnea and Endothelial Function in a Pediatric Population With Obesity

Abstract: BackgroundChildhood obesity has increased worldwide, becoming a significant public health concern. Brain-derived neurotrophic factor (BDNF) plays an important role in the central regulation of food intake and body weight, but little is known regarding its role in childhood obesity. Next to obesity, BDNF has been linked to obstructive sleep apnea (OSA) and endothelial dysfunction, two obesity-related comorbidities. The aim of this study is to investigate how BDNF, OSA and endothelial dysfunction interact in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…In addition, the association between circulating levels of BDNF and children with SDB is also still unclear. Consistent with our findings, Bahgat et (31,32). The results and patients were not evaluated in terms of OAHI ≥ 1 in these studies, which could explain the discrepancy in the results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the association between circulating levels of BDNF and children with SDB is also still unclear. Consistent with our findings, Bahgat et (31,32). The results and patients were not evaluated in terms of OAHI ≥ 1 in these studies, which could explain the discrepancy in the results.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, a significant difference was also found in serum BDNF levels between OSA children and PS children. In contrast, studies by Makhout et al and Wang et al have shown that BDNF levels are not affected by OSA in children ( 31 , 32 ). The results and patients were not evaluated in terms of OAHI ≥ 1 in these studies, which could explain the discrepancy in the results.…”
Section: Discussionmentioning
confidence: 79%
“…Our study didn’t find any significant differences in BDNF and proBDNF levels between OSA and the healthy control group. Interestingly, most human studies on BDNF in OSA showed no differences in BDNF levels [ 30 , 31 , 32 , 57 , 58 , 59 ]. On the other hand, Shah et al showed increased BDNF expression in the soft palate muscles of snorers and patients with OSA [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the groups were not age-matched, which should be taken into consideration. Regardless the available data on differences in the BDNF levels in similar comparisons in the literature is inconclusive, with the majority of studies similarly not noting any changes in the level of this protein [ 34 , 35 , 36 , 37 , 38 ]. In opposition are the results obtained by Flores et al, who, in their study, observed an increased level of the BDNF serum protein level in OSA patients compared to the control group [ 39 ].…”
Section: Discussionmentioning
confidence: 99%